2016
DOI: 10.1111/ics.12326
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐7 in the stratum corneum: a biomarker of the skin barrier function

Abstract: Measurement of scGal-7 content in tape-stripped samples was useful for the evaluation of the skin barrier function in dry skin conditions such as AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Measurement of galectin‐7 content in tape‐stripped stratum corneum samples from healthy human subjects showed that galectin‐7 increased after barrier disruption induced by sodium dodecyl sulphate. Additionally, stratum corneum galectin‐7 contents correlated with the values of transepidermal water loss, indicating the promoting function of galectin‐7 in skin barrier formation.…”
Section: Keratinocyte Differentiation and Skin Barrier Functionmentioning
confidence: 88%
See 1 more Smart Citation
“…Measurement of galectin‐7 content in tape‐stripped stratum corneum samples from healthy human subjects showed that galectin‐7 increased after barrier disruption induced by sodium dodecyl sulphate. Additionally, stratum corneum galectin‐7 contents correlated with the values of transepidermal water loss, indicating the promoting function of galectin‐7 in skin barrier formation.…”
Section: Keratinocyte Differentiation and Skin Barrier Functionmentioning
confidence: 88%
“…A study showed that the galectin‐7 level in stratum corneum of cheek skin was higher in patients with AD than in healthy controls and the level correlated with the total severity scores, as well as the erythema and pruritus in these areas …”
Section: Cutaneous Inflammationmentioning
confidence: 99%
“…Gal‐7 is a member of the β‐galactoside‐binding lectin family, playing a role in the maintenance of epidermal homeostasis. Gal‐7 could be used as a surrogate marker for transepidermal water loss (TEWL), and elevated levels of this protein may suggest skin barrier dysfunction …”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the results of a questionnaire survey of healthy volunteers, the SC Gal‐7 showed a higher expression in group C, leading to the presumption that the expression of SC Gal‐7 may be chronically increased in subjects who tend to have AV. The increased expression of Gal‐7 may cause hyperkeratosis, partially leading to the development of AV, as it reportedly reflects an impairment in skin barrier function and encourages re‐epithelialization . Increased SC Gal‐7 levels suggest the presence of the dry skin .…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of Gal‐7 in the skin is increased during epithelial differentiation . In preliminary studies, we analyzed the proteins that play a role in protecting the skin against damage agents, such as environmental stress . In this study, the usefulness of stratum corneum (SC) NGAL and SC Gal‐7 as biomarkers of AV is studied.…”
Section: Introductionmentioning
confidence: 99%